A SIMULATION ON TRAFFIC LIGHT CONGESTION - Abdul Khalil, Japar (Universiti Malaysia Sarawak (UNIMAS), 2020)
A traffic light is one of the efficient traffics control used to monitor the flow of vehicles. A congestion occurs when the volume of car is high than the road capacity. Other factors that will cause the congestion happened are due to the different driver’s behavior and the green time of traffic light that are not optimum enough to support the road demand. This study carry out to evaluate the current traffic light system and set a new standard traffic light signal timing to provide a better proposed system of traffic light. This can be achieved by undergo a simulation using a specific software